Nullspace of the m-th order discrete problem with nonlocal conditions - Paukštaitė, Gailė; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2016)
In this paper, we obtain the representation of the nullspace for m-th order discrete linear problems with nonlocal conditions. An example is given.The research was partially supported by the Research Council of Lithuania (grant No. MIP-047/2014).
Keywords: discrete problem; nonlocal conditions; nullspace